ANALISIS KINERJA ORGANISASI BADAN KESATUAN BANGSA DAN POLITIK KOTA SEMARANG - Nugrahinni S, Syaidatul; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2016)
The purpose of the research is to analyze the performance and determine the performance of the organization in Badan Kesatuan Bangsa dan Politik Kota Semarang. This research uses descriptive qualitative research. The location this study in Badan Kesatuan Bangsa dan Politik Kota Semarang. The qualitative data was obtained through a variety of techniques including data collection suck as interviews, document analysis, and literature. Selection of informants using the purposive technique. Data quality was tested using triangulation techniques. The phenomenon of organizational performance is measured from performance indicators, namely: productivity, quality of service, responsiveness and accountability. Organizational performance factors used are: human resources, organizational culture, and leadership. Performance Badan Kesatuan Bangsa dan Politik Kota Semarang in general need more repair, especially on the dimensions of productivity , namely an element of human resources, infrastructure and funding has not been used even less usefulness. The quality of service, employees do not yet have the required competencies and execution of tasks that are frequently incorrect, have not service strategy. responsiveness, need more repair constrained amount of human resources are lacking, the basic tasks and functions that are very much. Accountability still not good, not the web address as media transparency accountability to the public. The human factor is not well, they are often delaying work. Organizational culture still not good, professionalism is judged from the position not the work, and not good leadership, decision-making and the idea is often resolved by subordinates. Recommendations are given: (1) to improve the quality of human resources, by providing more education and training to employees such as computer training (2) to improve the quality of service by compiling standard operating procedures service (3) to immediately create a website address to increase the transparency of accountability (4) to gives limits subordinate to interfere in the decision-making without prohibiting subordinate ideas expressed opinions.